The impact of professional activity on the health status of healthcare managers - Romanova, Anna; Novitskaya, Svetlana; Tishchenko, Evgeny; Meshcharakov, Yurij (Polish Journal of Public Health, 2016)
Introduction. Currently, the work of managers is characterized by a number of factors having an unfavorable impact on human health. Stress as the main risk factor related to the professional activity is considered to be the major cause of possible poor health among the managers. Depression may result from a stress overload of managers.Aim. The authors wanted to determine the vulnerability to depression related to professional stress among healthcare managers and to assess gender and managerial work experience-specific differences.Materials and methods. A total of 235 healthcare managers working in the Republic of Belarus with various length of managerial work experience (women n=142, men n=93; mean age 45.7±1.21 years) underwent a psychological testing aimed at determining their vulnerability to depression. The results of the study were analyzed using the STATISTICA 7.0 software.Results. The vulnerability to depression in men differed from that in women (p=0.002). The predisposition to depression had significant differences between the groups with various experience of managerial work (p=0.03). The vulnerability to depression among healthcare managers increased with the length of managerial work. The highest level of vulnerability to depression was in healthcare managers with >20 years of experience (p=0.02) both in men (p=0.003) and in women (p=0.04).Conclusion. Thus, acquiring professional competences as a factor contributing to stress resistance, skills of coping with stress and alleviating its impact on the health status is very important through the whole professional activity. Healthcare managers with the length of work experience of 1-5 years are especially in need of the appropriate knowledge and skills.